Effects and costs of a multi-component menstrualhealth intervention (MENISCUS) on mental health problems, educational performance, and menstrual health in Ugandan secondary schools: an open-label, school-based, cluster-randomised controlled trial - Kate, Andrews Nelson; Stephen, Lagony; Kansiime, Catherine; Torondel, Belen; Clare, Tanton; Ndekezi, Denis; Mugenyi, Levicatus; Batuusa, Ratifah; Baleke, Christopher; Katherine, A. Thomas; Ssesanga, Titus; Bakanoma, Robert; et al. (The Lancet Global Health, 2025)
Background Menstrual health is a human rights issue, affecting mental health, wellbeing, and education. We assessed the effectiveness and costs of a school-based multi-component menstrual health intervention (“MENISCUS”) to improve mental health problems and educational performance. Methods We conducted a cluster-randomised trial in 60 Ugandan secondary schools, randomised 1:1 to the intervention or control condition (printed government menstrual health materials). The intervention included creating action groups, strengthening teacher-delivered puberty education, distributing menstrual kits, supporting student-led drama skits, providing pain-management strategies, and improving school water and sanitation facilities. Primary outcomes were mental health problems using the Strength and Difficulties Questionnaire (SDQ) Total Difficulties Score and independently-assessed educational performance. Secondary outcomes included menstrual knowledge, attitudes, practices, and self-efficacy, school attendance, confidence, symptomatic urinary tract infections, and quality of life in females, plus knowledge and attitudes in males. We estimated intention-to-treat intervention effects using mixed-effects models accounting for school clustering and adjusted for randomisation strata and baseline school-level means of outcomes. Registration: ISRCTN45461276. Findings Between 21 March and 5 July 2022, 3841 female students participated in baseline assessments (89.7% of those eligible) and between 5 June and 22 August 2023, 3356 participated in endline assessments. At endline, there was no evidence of a difference in mental health problems (mean SDQ score: 10.8 vs 10.7 in intervention vs control arms; adjusted mean difference [aMD] 0.05, 95% CI -0.40 to 0.50) or educational performance (mean z-score: 0.20 vs 0.12; aMD 0.05, 95% CI -0.11 to 0.20). There was strong evidence for effects on menstrual health-related outcomes. Interpretation Improving multiple dimensions of menstrual health in secondary schools in Uganda is feasible and important for health and human rights but is not sufficient to improve mental health or educational performance over one year.